DUNE Prospect for Leptophobic Dark Matter - Sabeeha Naaz; Jyotsna Singh; R. B. Singh (Advances in High Energy Physics)
Highly energetic proton/electron beam fixed-target experiments extend an opportunity to probe the sub-GeV dark matter and associated interactions. In this work, we have explored the sensitivity of DUNE (Deep Underground Neutrino Experiment) for sub-GeV leptophobic dark matter, i.e., this dark matter barely couples with the leptons. Baryon number gauge theory can predict the existence of leptophobic cold dark matter particle candidates. In our work, the dark matter candidate is considered to be scalar whose mass is defined by the symmetry breaking of new baryonic gauge group U1B. In this scenario, a light scalar dark matter couples with the standard model candidates via vector boson mediator VB which belongs to the baryonic gauge group U1B. This leptophobic dark matter dominantly couples to the quarks. Under this scenario, new parameter space for αB is explored by DUNE for leptophobic dark matter candidates. This new parameter space allowed αB to get a lower value than the present exiting constraint value of αB, i.e., 10−6.